The Influence of Social Media and Visual Content on Customer Engagement on Shopee E-commerce - Yuliana, Liza; Sanny EDINOV (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigates the impact of social media marketing and visual content as key variables in driving customer engagement on the Shopee e-commerce platform. With the rapid growth of the digital economy, brands' ability to effectively engage with their customers through digital channels is crucial. Using a quantitative approach, this study collected data through a questionnaire distributed to 100 respondents, who were active users and followers of Shopee's social media accounts. Social media variables were measured based on the frequency and quality of interactions on platforms such as Instagram, TikTok, and Facebook. Meanwhile, visual content variables were assessed based on the attractiveness, informativeness, and uniqueness of posted product photos and videos. Customer engagement variables were measured through interaction indicators such as likes, comments, shares, and participation in promotions. The results of a multiple regression analysis showed that both variables, namely social media and visual content, had a positive and significant influence on customer engagement, both partially and simultaneously. Specifically, these findings highlight that the quality of visual content plays a more dominant role in triggering customer interaction. Visual content that is aesthetically designed and provides clear information is proven to be more effective in building emotional connections and sustained interactions. The implications of this study offer strategic insights for Shopee marketing teams and other e-commerce players, emphasizing the importance of optimal resource allocation to produce creative and engaging visual content, as well as personalizing interactions on social media to build stronger customer loyalty.